Determination of Lead Level (Pb) in Garage Worker’s Hair Using Atomic Absorption Spectroscopy (AAS) - Dyah Wulandari, Devyana; Putri, A.M; Handayani, Handayani (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Pb is a heavy metal produced from the combustion of fuels that does not decompose or burn completely. Heavy metals in the human body usually accumulate in several organs such as kidneys, liver, nails, adipose tissue, and hair. This study aims to determine the level of lead and find out the use of masks in workshop workers in the Sidoarjo area. This research was conducted on garage workers in the Sidoarjo region with the number of respondents 27 people using hair samples and measuring Pb levels using the Atomic Absorption Spectrophotometer (AAS) method with supporting data in the form of questionnaires. Based on the results of research obtained on garage workers who did not use masks, the average yield of lead (Pb) of 46.9 μg / g and the garage workers using masks obtained a mean lead level (Pb) of 34.3 μg / g. Based on statistical analysis, the results showed that there were no significant differences in Pb levels between respondents who used masks and respondents who did not use masks. The conclusion obtained from the results of this study is that there were no statistically significant differences in Pb levels between respondents who used masks and respondents who did not use masks in garage workers in the Sidoarjo region.